2015
DOI: 10.12688/f1000research.7161.1
|View full text |Cite
|
Sign up to set email alerts
|

Validating the use of Medicare Australia billing data to examine trends in skin cancer

Abstract: Background:  Epidemiological data surrounding non-melanomatous skin cancer (NMSC) is highly variable, in part due to the lack of government cancer registries. Several studies employ the use of Medical Australia (MA) rebate data in assessing such trends, the validity of which has not been studied in the past. Conversely, melanoma skin cancer is a notifiable disease, and thus, MA and cancer registry data is readily available. The aim of the current study is to assess the use of MA for epidemiological measures fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…32 To address this limitation, individuals who received health care services under the Department of Veteran's Affairs program were excluded from the study. 40 Additionally, the aged care eligibility assessment used to ascertain the history of skin cancer and cataract only records up to 10 health conditions; the aged care eligibility assessors only report those conditions that have been diagnosed by a suitably qualified individual and impact on the person's need for assistance. 41 It is possible that neither cataract nor skin cancer were listed.…”
Section: Discussionmentioning
confidence: 99%
“…32 To address this limitation, individuals who received health care services under the Department of Veteran's Affairs program were excluded from the study. 40 Additionally, the aged care eligibility assessment used to ascertain the history of skin cancer and cataract only records up to 10 health conditions; the aged care eligibility assessors only report those conditions that have been diagnosed by a suitably qualified individual and impact on the person's need for assistance. 41 It is possible that neither cataract nor skin cancer were listed.…”
Section: Discussionmentioning
confidence: 99%
“…A validation study of MBS data with linked Queensland KC cases demonstrated the overall reliability of using Medicare claims for identifying KC, as approximately 88% were identified when using the primary excision, cryotherapy or serial curettage items for KC treatment 10 . MBS data are also suitable for assessing epidemiological trends in skin cancer 11 …”
Section: Methodsmentioning
confidence: 99%
“…Such data requires the accurate billing by surgeons and administrators associated with each respective case. Despite these concerns, MBS‐based data has been validated for use in the setting of various procedures, including melanoma excision, by comparing frequencies to the respective cancer registries . Further, data on billings from public sector was not available for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these concerns, MBSbased data has been validated for use in the setting of various procedures, including melanoma excision, by comparing frequencies to the respective cancer registries. 33 Further, data on billings from public sector was not available for analysis. Due to limitations in MBS data, information pertaining to oncological (final pathology, pathological stage), patient (comorbidities, renal function), peri-operative (operative approach, Da Vinci generation, conversion rate and reason, RAPN age and gender specific details) and social (socioeconomic status, private health insurance coverage, geographical location) were not available for analysis, making definitive conclusions for the trends observed or comparisons to other cohorts difficult.…”
Section: Discussionmentioning
confidence: 99%